CHILDREN IN POST-WAR VIENNA IN JOSEPH ROTH'S FEUILLETONS 1919–1920 - Monolatii, T. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article is devoted to the study of the characteristics of the depiction of the place and role of children in the conditions of post-war Vienna by the classic of Austrian literature of the 20th century, a native of Brody in Galicia, Joseph Roth (1894–1939), on the pages of the left-liberal local newspaper “Der Neue Tag” in 1919–1920. The external background of the investigated problem is the disintegration of the national-state order of pre-war Europe, the destruction of former value and cultural structures, the fate of the “lost generation”. It is argued that these factors reflected the situation of homelessness, absolute alienation and emptiness in the individual, social and metaphysical sense of the nameless heroes of J. Roth's feuilletons, which can be considered as the author's journalistic reaction to the social problems of the investigated chronotope. It is noted that most of the analyzed texts of J. Roth were published in the thematic newspaper column “Viennese symptoms”, dedicated in particular to descriptive problems of children of the poorest and most vulnerable strata of the urban population of the capital of the Republic of Austria. As a journalist, J. Roth points out the miserable conditions of their lives, social suffering and his own indignation at the inaction of government institutions regarding the fact that orphans do not attend educational institutions. It is emphasized that in the analyzed feuilletons, J. Roth spoke with great enthusiasm about the educational reform of 1919-1934 of the Austrian social-democrat politician, reformer of school education Otto Glöckel, believing that its implementation will change the Austrian youth, who will oppose extreme political ideologies. It turns out that based on the study of the experiences of individual families in the feuilletons of J. Roth; it is possible to assert certain regularity in the future development of children, their actual destiny to repeat the fate of their parents. It is concluded that the depiction of children in the conditions of post-war Vienna in the feuilletons of the future Austrian classic can be considered a special example of the interweaving of contemporary problems of morality, local politics and school education, determined by the subjectivism of J. Roth as a young journalist.